(untitled) (CIPEEX, 2025)
Hippotherapy is an equine-assisted therapy that began in 1989 by the National Association of Hippotherapy (ANDE), which uses the horse in direct contact with the child, contributing positively to the improvement of the practitioner and fostering greater biopsychosocial development. Hippotherapy is used in the treatment of various sensory-motor pathologies such as cerebral palsy, sensory deficits, maturational delay, and others. The objective of this study was to survey the epidemiological profile of hippotherapy practitioners and the motor and cognitive development of practitioners with neuropediatric disorders, in the rehabilitation phase at a hippotherapy center in the municipality of Ceres-GO. This is a cross-sectional study, of an exploratory and descriptive nature, regarding the epidemiological profile and motor and cognitive development of Hippotherapy practitioners in the rehabilitation phase. Data collection was performed using a sociodemographic questionnaire and the Pediatric Evaluation of Disability Inventory (PEDI). Twenty-nine practitioners were studied, with a majority being male (79.6%), with a mean age of 8.65 ([+].underline10.55). The most prevalent diagnosis was Autism Spectrum Disorder (ASD) with 55.2% of practitioners, followed by attention deficit and hyperactivity disorder (ADHD) with 20.7%. The practitioners presented moderate impairment in motor and cognitive development, with ASD showing the greatest impairment in social function. The survey made it possible to draw a detailed map of neurological, cognitive, and physical dysfunctions, which supports decision-making and directs safe intervention for practitioners, and greater efficacy of hippotherapy.